Active Surveillance of Influenza A and Other Respiratory Viruses in Children with Influenza-like-illness in Two Seasons - Girit, Saniye; Karaaslan, Ayşe; Gençer, Serap; Yılmaz, Emel; Ayhan, Yetkin; Vayvada, Elif Ruşen; Akçay Ciblak, Meral; Badur, Selim; Akın, Yasemin (The Journal of Infection in Developing Countries, 2018)
Introduction: The aim of this study was to asses the surveillance of influenza A/other respiratory viruses and risk factors in hospitalized children with the symptoms of influenza-like illness during two consecutive influenza seasons. Methodology: All children hospitalized with adiagnosis of influenza-like illness had been investigated for Influenza A and other respiratory antigens in pharengeal/nasopharyngeal secretions. Results: A total of 132 hospitalized children between December 2013-May 2014 and December 2014-May 2015 were enrolled in this study. At least one respiratory virus was found to be positive by RT-PCR in 78 (59%) patients, influenza A (H3N2) was detected in only 8 (6%) patients. In 54 (41%) patients samples no respiratory viral pathogen was detected and in 70 (53%) patients, one non- influenza A virus was detected. The respiratory viral pathogens detected in decreasing rates were:RSV (n = 46, 35%), HCoV (n = 10, 7.5%), adenovirüs (n = 7, 5%), rhinovirüs (n = 6, 4.5%), HMPV (n = 5, 4%), Influenza B (n = 4, 3%) ve human Bocavirus (n = 2, 1.5%). In 10 patients, coinfection was detected, however none was with H3N2. In the H3N2 (+) group, the following risk factors were identified: age older than three years (p < 0.05), asthma history (p < 0.05) and chronic lung diseases (p < 0.05). Conclusion: Influenza A virus was detected in 6% of hospitalized patients with influenza-like illness. Viruses other then Influenza, especially RSV, can cause similar symptoms compatible with Influenza-like-illness.